Healthcare providers knowledge and attitudes toward abortion care in Ibadan, Nigeria - Makelele, Amos M.; Shimilimo, Agness; Solomon, Million T.; Elioba, John L. R.; Obajimi, Gbolahan O.; Olayemi, Oladapo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: In settings with limited resources, abortion care plays a crucial role in reducing maternal mortality rates and ensuring comprehensive healthcare. In Sub-Saharan Africa, over 70% of abortions are classified as unsafe. In Nigeria, restrictive laws and social stigmas shape healthcare providers’ knowledge and attitudes toward abortion care. Methods: This study employed a cross-sectional study design to assess healthcare providers’ knowledge, attitudes, and practices regarding abortion care at the University College Hospital, Ibadan-Nigeria’s first tertiary hospital. Data was analysed using IBM statistical package for the social sciences (SPSS) version 25. Descriptive statistics were generated and presented as frequency tables and pie charts. A p value of <0.05 was regarded as statistically significant. Results: While 63% of providers demonstrated adequate knowledge of abortion care, significant gaps persisted, particularly regarding legal provisions and post-abortion care. Despite 86% supporting access to safe abortion under specific circumstances, personal and religious beliefs influenced their willingness to provide services. Conclusions: Addressing knowledge gaps and mitigating personal biases through targeted training, policy advocacy, and community engagement is essential for improving abortion care, reducing unsafe procedures, and enhancing maternal health outcomes in Nigeria.